A simplified T classification based on the 8th edition of the UICC/AJCC staging system for nasopharyngeal carcinoma - Pan, Xing-Xi (Cancer Manag Res, 2019)
Objective: This study aimed to establish a simplified T classification based on the 8th edition of the Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) staging system for nasopharyngeal carcinoma (NPC). Methods: In total, 325 patients with NPC were included in this study. All patients underwent magnetic resonance imaging, and the staging criteria were recorded. These patients were subjected to staging with the 8th edition of the UICC/AJCC staging system for NPC. Results:  Involvement of the oropharynx, nasal cavity, adjacent soft tissue (medial pterygoid, lateral pterygoid, and prevertebral muscles), cervical vertebra, orbit, and hypopharynx were always accompanied by other equivalently or more advanced T-stage classifications. All cases with involvement of the paranasal sinuses showed skull base erosion. The majority of cases with involvement of the pterygoid structure showed skull base erosion. Conclusion: According to the simplification principle, the following new T classification based on the 8th edition of the UICC/AJCC staging system was established: T1, tumor confined to nasopharynx, or beyond the nasopharynx without parapharyngeal involvement; T2, tumor with extension to the parapharyngeal space; T3, tumor with infiltration to bony structures at the skull base; T4, tumor with intracranial extension, involvement of the cranial nerves or parotid gland, and/or extensive soft tissue infiltration beyond the lateral surface of the lateral pterygoid muscle. Validation with a large series of patients is needed.